DEVELOPMENT OF ANALYTICAL AND CREATIVE SKILLS OF FUTURE TEACHERS BASED ON A MODERN DIDACTIC APPROACH - Муминова Гюльхайя Тургунбай кызы (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article will analyze how to develop analytical and creative skills of future teachers based on modern didactic approaches. The article considers various aspects of didactic approaches, pedagogical methods of teachers and methods used in the process of developing analytical and creative skills.